FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS - Neneng Sri Suprihatin; Lulu Naifaroh; Dita Fazarwati (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
The purpose of study was to examine the effect of board composition, agency cost, liquidity, leverage and firm size on financial distress in sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 Period. This research a quantitative method. The population in this study are various industrial sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period. The sample research method was carried out using the purposive sampling method, based on predetermined criteria there were 13 companies used as samples. The analytical method used is the method of logistic regression analysis. The test results show that: (1) board composition has no effect on financial distress, (2) agency cost has no effect on financial distress, (3) liquidity has no effect on financial distress, (4) leverage has no effect on financial distress, (5) firm size has no effect on financial distress.